PENGARUH KEPEMIMPINAN VISIONER KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMA NEGERI 5 KARAWANG - Ainun Nisa, Putri; Iqbal Amar Muzaki; Chairil Fajar Hadiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the principal's visionary leadership on teacher performance at SMA Negeri 5 Karawang. The research used a quantitative causal-associative approach with a saturated sample of 59 teachers. Data were collected through questionnaires, observation, and documentation, then analyzed using descriptive statistics, classical assumption tests, Pearson product moment correlation, simple linear regression, t-test, and coefficient of determination with IBM SPSS 25. The results show that the principal's visionary leadership is in the very good category with an average score of 3.59, while teacher performance is also in the very good category with an average score of 3.42. The correlation test produced r = 0.679 with Sig. = 0.000, indicating a strong and significant relationship. The regression equation is Y = 10.537 + 0.539X, and the t-test result shows tcount = 6.978 > ttable = 2.002 with Sig. = 0.000. The coefficient of determination is 0.461, meaning that visionary leadership contributes 46.1% to teacher performance, while 53.9% is explained by other factors not examined in this study. These findings indicate that the principal's visionary leadership has a positive and significant effect on teacher performance.